Pancreatic Metastasis of High-Grade Papillary Serous Ovarian Carcinoma Mimicking Primary Pancreas Cancer: A Case Report. (8th July 2012) - Gunay, Yusuf; Demiralay, Ebru; Demirag, Alp
Abstract : Introduction . Reports of epithelial ovarian carcinomas metastatic to the pancreas are very rare. We herein present a metastasis of high grade papillary serous ovarian cancer to mid portion of pancreas. Case . A 42-year-old patient was admitted with a non-specified malignant cystic lesion in midportion of pancreas. She had a history of surgical treatment for papillary serous ovarian adenocarcinoma. A cystic lesion was revealed by an abdominal computerized tomography (CT) performed in her follow up . It was considered as primary mid portion of pancreatic cancer and a distal pancreatectomy was performed. The final pathology showed high-grade papillary serous adenocarcinoma morphologically similar to the previously diagnosed ovarian cancer. Discussion . Metastatic pancreatic cancers should be considered in patients who present with a solitary pancreatic mass and had a previous non-pancreatic malignancy. Differential diagnosis of primary pancreatic neoplasm from metastatic malignancy may be very difficult. A biopsy for tissue confirmation is required to differentiate primary and secondary pancreatic tumors. Although, the value of surgical resection is poorly documented, resection may be considered in selected patients. Conclusion . Pancreatic metastasis of ovarian papillary serous adenocarcinoma has to be kept in mind when a patient with pancreatic mass has a history of ovarian malignancy.